Localization of Brain Natriuretic Peptide Immunoreactivity in Rat Spinal Cord - Abdelalim, Essam M.; Bellier, Jean-Pierre; Tooyama, Ikuo (Frontiers in Neuroanatomy, 2016)
Brain natriuretic peptide (BNP) exerts its functions through NP receptors. Recently, BNP has been shown to be involved in a wide range of functions. Previous studies reported BNP expression in the sensory afferent fibers in the dorsal horn (DH) of the spinal cord. However, BNP expression and function in the neurons of the central nervous system are still controversial. Therefore, in this study, we investigated BNP expression in the rat spinal cord in detail using reverse transcription-polymerase chain reaction (RT-PCR) and immunohistochemistry. RT-PCR analysis showed that BNP mRNA was present in the spinal cord and dorsal root ganglion (DRG). BNP immunoreactivity was observed in different structures of the spinal cord, including the neuronal cell bodies and neuronal processes. BNP immunoreactivity was observed in the DH of the spinal cord and in the neurons of the intermediate column (IC) and ventral horn (VH). Double-immunolabeling showed a high level of BNP expression in the afferent fibers (laminae I–II) labeled with calcitonin gene-related peptide (CGRP), suggesting BNP involvement in sensory function. In addition, BNP was co-localized with CGRP and choline acetyltransferase (ChAT) in the motor neurons of the VH. Together, these results indicate that BNP is expressed in sensory and motor systems of the spinal cord, suggesting its involvement in several biological actions on sensory and motor neurons via its binding to NP receptor-A (NPR-A) and/or NP receptor-B (NPR-B) at the spinal cord level.